Adams-Oliver syndrome: a case with full expression - Amir Dehdashtian; Masoud Dehdashtian (MDPI AG, 2016)
Adams-Oliver syndrome (AOS) is characterized by the combination of congenital scalp defects (aplasia cutis congenita) and terminal transverse limb defects of variable severity. It is believed that Adams-Oliver syndrome without major organ abnormalities does not necessarily alter the normal lifespan. We present a case without detectable major organ abnormality contrary to life but with poor weight gain. A male infant with scalp and skin cutis aplasia, generalized cutis aplasia, dilated veins over scalp and trunk, hypoplastic toes and nails of feet, glaucoma, poor feeding and poor weight gain. This report shows a case of AOS without major multiple organ abnormalities but with poor feeding and abnormal weight gain that may be alter the normal lifespan.